Health and toxicology - Cheremisinoff, Paul N.; Bacis, M. (Advances in environmental control technology., 1997)
This addition to the Advances in Environmental Control Technology Series contains 23 chapters designed to provide an extensive overview and reference on human physiological responses to various forms of pollution.